Selective Hydrogenation of Dodecanoic Acid to Dodecane-1-ol Catalyzed by Supported Bimetallic Ni-Sn Alloy - Rodiansono Rodiansono; Muhammad Iqbal Pratama; Maria Dewi Astuti; Abdullah Abdullah; Agung Nugroho; Susi Susi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
Selective hydrogenation of dodecanoic acid over supported bimetallic Ni-Sn alloy catalysts into dodecane-1-ol is demonstrated. Bimetallic nickel-tin supported on titanium oxide (Ni-Sn(1.5)/TiO2) and gamma-alumina (Ni-Sn(1.5)/g-Al2O3); 1.5 = Ni/Sn molar ratio) were synthesized via hydrothermal method in a sealed-Teflon autoclave reactor at 150 oC for 24 h, then followed by reducing with hydrogen gas at 400 oC for 1.5 h. The synthesized catalysts were characterized by means of XRD, IC-AES, N2-adsorption (BET method), H2-chemisorption, and NH3-TPD. Bimetallic Ni-Sn(1.5)/TiO2 catalyst was found to be effective for hydrogenation of dodecanoic acid (>99 % conversion) to dodecane-1-ol (93% yield) at 160 oC, 30 bar H2, and 20 h and the highest dodecane-1-ol (97 % yield) was obtained at initial pressure of H2, 50 bar. An increase of reaction temperature slightly enhanced the degree of hydrodeoxygenation of dodecanoic acid to produce dodecane over both Ni-Sn(1.5)/TiO2 and Ni-Sn(1.5)/g-Al2O3 catalysts.